The The Level of Satisfaction of inpatients and outpatients with Pharmaceutical Installation Services in Arifin Ahmad Hospital - Adrian Mulya; Denia Pratiwi; Novika Indriani; Nurul Fadhilah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Quality healthcare services are characterized by the satisfaction of the needs and expectations of all patients. The level of patients satisfaction is also largely dependent on the quality of services provided by hospitals and can be measured by 5 dimensions, namely reliability, responsiveness, assurance, empathy, and tangible. Therefore, this study aimed to determine the level of inpatients and outpatients satisfaction with pharmaceutical services at the pharmacy depot of Arifin Achmad Hospital in Pekanbaru. The study procedures were carried out using a descriptive observational method with a Cross-Sectional design. The sample population comprised 95 inpatients and 100 outpatients who were selected using purposive sampling and interviewed with a questionnaire. The data collected were then analyzed descriptively using univariate and bivariate analysis with computer software. The results showed that the level of inpatients satisfaction with services obtained an average score of 92.31%, 80.35%, 92.91%, 90.07%, and 85.15% for reliability, responsiveness, assurance, empathy, and tangible dimensions, respectively. Meanwhile, outpatients satisfaction showed an average score of 83.24%, 75.99%, 87.42%, 85.14%, and 88.18% for reliability, responsiveness, assurance, empathy, and tangible dimensions, respectively. Based on these findings, patients were highly satisfied with pharmacy installation services with an overall average score of 88.75% for inpatients care and 84.68% for outpatients care across all dimensions.